Komunitas Nematoda pada Tanaman Kopi (Coffea Canephora Var. Robusta) Muda di Kabupaten Tanggamus Lampung - SWIBAWA, I GEDE (Agrotrop : Journal on Agriculture Science; Vol 4 No 2 (2014), 2015)
The Community of Nematode in The Young Coffee ( Coffea Canephora Var. Robusta ) Crops in Tanggamus District, Lampung. Tanggamus district is one of coffee production center in Lampung province. Since year of 2013, farmers in Tanggamus have been replaced the unproductive old coffee by coffee seed introduced from East Java. Introducing coffe seed from outside area at risk of carrying plant parasitic nematodes. The purpose of this research was to study community of nematode associated with young coffee crops in Tanggamus. Survey was conducted in coffee robusta (Coffea canephora var. robusta) fields belonging to farmer on September 2014. Soil samples were collected from three sites: Margo Mulyo, Sumber Rejo and Batu Bedil. Nematodes were extracted by sieving and centrifugation with sugar solution method. The results show that were 20 genera consisted of 9 genera of plant parasitic and 11 genera of free living nematodes associated with young coffee in Tanggamus. The nematode community was dominated by Pratylenchus and Radopholus. The population of Pratylenchus and Radopholus in Sumber Rejo site were 421 and 846 individual per 300 ml of soil respectively. It was needed to indentify up to species taxonomic level for Pratylenchus and Radopholus associated with young coffee in Tanggamus.
Keywords: Nematodes; Robusta coffee; Tanggamus Lampung